2009
DOI: 10.1161/circheartfailure.109.862664
|View full text |Cite
|
Sign up to set email alerts
|

Development of Left Ventricular Diastolic Dysfunction With Preservation of Ejection Fraction During Progression of Infant Right Ventricular Hypertrophy

Abstract: Background Progressive left ventricular (LV) dysfunction can be a major late complication in patients with chronic right ventricular (RV) pressure overload (e.g., tetralogy of Fallot). We therefore examined LV function (serial echocardiography and ex vivo Langendorff) and histology in a model of infant pressure-load RV hypertrophy (RVH). Methods and Results Ten-day-old rabbits (N=6 per time point, total = 48) that underwent pulmonary artery banding (PAB) were sacrificed at 2–8 weeks after PAB, and comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
8
34
0
Order By: Relevance
“…11,15,19) In this study, RVFAC in the PAB group decreased from 3 weeks postoperatively ( Figure 2D), as RVMPI increased during the same period after surgery ( Figure 2E). The RV free wall in diastole thickened from 4 weeks after operation ( Figure 2F).…”
Section: Morphologysupporting
confidence: 52%
See 2 more Smart Citations
“…11,15,19) In this study, RVFAC in the PAB group decreased from 3 weeks postoperatively ( Figure 2D), as RVMPI increased during the same period after surgery ( Figure 2E). The RV free wall in diastole thickened from 4 weeks after operation ( Figure 2F).…”
Section: Morphologysupporting
confidence: 52%
“…11,22) Clinically, long-term RV hypertension causes various complications in some congenital diseases such as surgically repaired tetralogy of Fallot. 5,6) The increased stress on the RV limits long-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, others described the "working heart" model, in which the myocardium performs both pressure and volume work. 2 Such preparations have been instrumental in elucidating mechanisms of myocardial action, 3 myocardial metabolism, [4][5][6] and effects of cardiotonic medications. [7][8][9] The use of medications that enhance myocardial contractility is common in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that changes in cardiomyocyte viability, lack of adaptive capillary growth, fibrosis, and response to metabolic stress are differentially regulated in LV-AOB and RV-PAB (11,13,16,20). However, the mechanisms involved in the compensated phase of LV-AOB and RV-PAB have yet to be clearly elucidated.…”
mentioning
confidence: 97%